2009
DOI: 10.1128/jcm.00130-09
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Screening Tests for Suspected Class A Carbapenemase Production in Species of Enterobacteriaceae

Abstract: The detection of class A serine-carbapenemases among species of Enterobacteriaceae remains a challenging issue. Methods of identification for routine use in clinical microbiology laboratories have not been standardized to date. We developed a novel screening methodology suitable for countries with high basal levels of carbapenem resistance due to non-carbapenemase-mediated mechanisms and standardized several simple confirmatory methods that allow the recognition of bacteria producing class A carbapenemases, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
0
16

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(208 citation statements)
references
References 22 publications
(28 reference statements)
5
182
0
16
Order By: Relevance
“…Previously, a flowchart for the detection of KPC, using the VITEK 2 system, determined that a minimum inhibitory concentration for imipenem ≥ 2 and meropenem ≥ 1 provided a sensitivity of 98%, a specificity of 94%, and a PPV of 95% to detect KPC [16]. Several studies have shown that the boronic acid test has a sensitivity of 89%-100%, a specificity of 100%, a PPV of 100%, and a NPV of 100% for the detection of KPC [14,21]. However, very few reports have described the pragmatic application of the boronic acid test during outbreaks of KPC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a flowchart for the detection of KPC, using the VITEK 2 system, determined that a minimum inhibitory concentration for imipenem ≥ 2 and meropenem ≥ 1 provided a sensitivity of 98%, a specificity of 94%, and a PPV of 95% to detect KPC [16]. Several studies have shown that the boronic acid test has a sensitivity of 89%-100%, a specificity of 100%, a PPV of 100%, and a NPV of 100% for the detection of KPC [14,21]. However, very few reports have described the pragmatic application of the boronic acid test during outbreaks of KPC.…”
Section: Discussionmentioning
confidence: 99%
“…The primers used were the following: 5′-AACAAGGAATATCGTTGATG-3′ and reverse primer 5′-AGATGATTTTCAGAGCCTTA-3′ (Integrated DNA Technologies, Coralville, USA). The combined-disk boronic acid test, containing 300 µg of 3-aminophenyl-boronic acid (APBA), was used as a confirmatory test in phase two for the detection of KPC (catalogue code B1241627, Britania Laboratory, Buenos Aires, Argentina) [14], only after the diagnostic accuracy was determined from January 2011-May 2011 (phase one) by comparing it to the PCR test results in 131 samples. An imipenem disk (10 µg) with a distance of 20 mm was used for APBA inhibition.…”
Section: Tests For the Detection Of K Pneumoniae And Kpcmentioning
confidence: 99%
See 1 more Smart Citation
“…Se realizó mediante los métodos de Hodge modificado 19 , sinergia con ácido fenil borónico (AFB) 21 23 . Los productos de amplificación se sometieron a electroforesis en gel de agarosa al 2%, luego se colorearon con bromuro de etidio (0,5 μg.ml -1 ) en tampón TBE 1X, durante 30 min a 10 V.cm -1 .…”
Section: Detección De Carbapenemasas Por Métodos Fenotípicosunclassified
“…Pasteran e colaboradores no ano 2009 pesquisaram a efetividade desse método para a deteção de todas as carbapenemases de classe A, obtendo novas recomendações para a triagem destas enzimas (Pasteran, et al, 2009 (Yigit et al, 2003, Wolter, et al, 2008, Girlich et al, 2008, Woodford et al, 2007. A cepa Kp-13 teve este comportamento característico associado à presença da enzima KPC, porém a cepa Kp-35 apresentou uma resistência maior para o imipenem (CIM = 128 µg/mL), ertapenem e meropenem (CIM ≥512 µg/ml).…”
Section: Discussionunclassified